(untitled) (Journal of Philosophy Culture and Political Science, 2023)
Using examples of the construction of mosques in the capital, the article shows how the discourse of the importance of Islam for cultural memory manifests itself through the practice of forming new public spaces. Despite the fact that, in comparison with the general Kazakh trends, the increase in the number of mosques in Astana is not so significant, each new mosque in the capital is formed as a unique of case, where, in addition to the main religious issues, one can also trace: state policy in the field of cultural memory; the growth of emotional, symbolic and infrastructural load on mosques; the increasing role of participation in the spaces of the mosque. Every decade, not only the main cathedral mosques, larger and larger in terms of its size, are being opened in the capital, but also the primary infrastructural linking of mosques to different urban spaces takes place. The article also discusses the question of who is the actor of the emergence of these new mosques. One of the examples of the "diplomacy of mosques" was the Nur-Astana mosque built at the expense of a foreign investor; by order of representatives of the political elite and local communities, projects of Islamic religious buildings, unique in its architectural solutions, were implemented. The article uses an infrastructural approach, which made it possible to identify important aspects in the topography of mosques in the metropolitan area, in the specifics of relations between state authorities, patrons, Muslim clergies and other interested parties that have a direct impact on the strengthening and development of mosques as important public spaces. There has also been an increase in the practices of opening Islamic culture museums at mosques in the last decade, which contributes to the transformation of the usual image of the mosque and strengthening their importance in the mass consciousness as an important object of cultural memory infrastructure. Key words: infrastructural approach, memory infrastructure, cultural landscape, mosque, public space, Astana, Spiritual Administration of Muslims of Kazakhstan.